2016
DOI: 10.1142/s1793604716300036
|View full text |Cite
|
Sign up to set email alerts
|

The research progress of Li-ion battery separators with inorganic oxide nanoparticles by electrospinning: A mini review

Abstract: The technology of Lithium-ion battery (LIB) separator has become more and more mature. But there are still many problems that needed to be resolved. For example, its mechanical strength is low relatively, thermal stability is bad and the porosity and electrochemical performance are imperfect. This paper introduces modification of electrospinning LIB separator from the way of adding nanoparticles, including SiO2, TiO2, Al2O3 and copper titanate oxide, etc. And addition methods include dissolving in dispersant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…31,32 To the best of our knowledge, the introduction of hydrophilic inorganic nanoparticles is one of the best ways for enhancing the wettability of the separators. 33,34 However, the inorganic nanoparticle coating will unavoidably raise the total thickness and mass, resulting in the blockage of some micropores of the separators and additional decay to ion-transport performance and power density. Additionally, mixing inorganic nanoparticles with the film matrix directly in the synthesis process would lead to the decrease of mechanical strength of the separators and low utilization ratio of inorganic nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 To the best of our knowledge, the introduction of hydrophilic inorganic nanoparticles is one of the best ways for enhancing the wettability of the separators. 33,34 However, the inorganic nanoparticle coating will unavoidably raise the total thickness and mass, resulting in the blockage of some micropores of the separators and additional decay to ion-transport performance and power density. Additionally, mixing inorganic nanoparticles with the film matrix directly in the synthesis process would lead to the decrease of mechanical strength of the separators and low utilization ratio of inorganic nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, to solve the wettability problem of commercial separators, tremendous surface modification techniques have been carried out, including hydrophilic polymer coatings, polydopamine treatment, and plasma modification. Inorganic/polymer hybrid films and inorganic/polymer/inorganic trilayer films also have been fabricated for solving the poor thermostability and wetting performance. , To the best of our knowledge, the introduction of hydrophilic inorganic nanoparticles is one of the best ways for enhancing the wettability of the separators. , However, the inorganic nanoparticle coating will unavoidably raise the total thickness and mass, resulting in the blockage of some micropores of the separators and additional decay to ion-transport performance and power density. Additionally, mixing inorganic nanoparticles with the film matrix directly in the synthesis process would lead to the decrease of mechanical strength of the separators and low utilization ratio of inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Solution parameters, including molecular weight, solution viscosity, solution conductivity; environmental parameters, such as temperature, humidity; and processing parameters, such as voltage, flow rate, the morphology of collector and tip-collector distance would influence the morphology of nanofibers [77]. The research progress on nanofibers using electrospinning were demonstrated for applications in nanomedicine [78] and Li-ion battery separators [79] with properties, such as large surface area and high porosity yielding high loading capacity, high encapsulation efficiency, and low preparation cost.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…When served as an anode material for LiBs, the capacity of the paper only reduced from ∼175 to ∼125 mAh g –1 from the 2nd to the 500th cycles at 3960 mA g –1 . Moreover, recently reported reviews suggested the main advantages of electrospinning technology in the preparation of LiB materials with a nanoactive-particle-coated structure, which were listed as follows: ,, (1) Ease of choosing spinning raw materials, because the carbon source can be derived from various soluble polymers; (2) most of the electrode materials are soluble in polymer solution; (3) the structures of the spinning products can be finely tailored in terms of the diameter, density, solid/hollow, and multilayer coaxial structure of the fibers; (4) the fibers featured an interpenetrating network structure, and it is easy to obtain electrode materials with excellent performance through a simple heat treatment process; and (5) the fiber filaments with an interconnected structure can be easily soaked in an electrolyte and thus will lead to a fast Li + transfer rate when compared with the traditional powder-based electrode materials. In addition to electrospinning, it is suggested that one can also synthesize nanocomposites toward superior electrochemistry activity, highly efficient hydrogen evolution, overall water splitting, and so on, by incorporating a similar fine structural design strategy. …”
Section: Introductionmentioning
confidence: 99%